Dynamic setpoint control for museum indoor climate conditioning integrating collection and comfort requirements: Development and energy impact for Europe. (June 2017) - Kramer, Rick; van Schijndel, Jos; Schellen, Henk
Abstract: This study presents a seven-step algorithm for hourly setpoint calculation of museums' indoor temperature ( T i ) and relative humidity ( RH i ) integrating collection requirements (ASHRAE) and thermal comfort requirements. Moreover, building energy simulation results provide insight into the energy impact of five levels of museum indoor climate conditioning applied to four building quality levels (ranging from a historical building to a purpose-built museum building) using weather data from twenty locations throughout Europe. The five levels of indoor climate conditioning were calculated using the presented setpoint algorithm, a validated simulation model of museum Hermitage Amsterdam was adjusted to represent the four building quality levels, and technical-reference-year (TRY) weather data of twenty locations were used. The conclusions: The setpoint algorithm enables smooth control of seasonal adjustments, integrated with permissible short fluctuations of T and RH (according to ASHRAE classes); improving the building quality quickly follows the law of diminishing returns; supposing to result in the same collection risk, subclass Ad (no seasonal adjustments, but larger hourly fluctuations) is more energy efficient than subclass As (with seasonal adjustments, but smaller hourly fluctuations) for most locations; although class AA is more stringent than subclass As, class AA appears to require less energy than subclass As for some locations, due to efficiency differences of the humidification and dehumidification processes. Graphical abstract: Highlights: A setpoint algorithm is presented integrating collection and comfort requirements. The energy impact is assessed of five levels of museum indoor climate control. Four building types and twenty locations in Europe are included. The results may help many museums to choose an appropriate climate class. A significant energy saving potential has been demonstrated for many museums.